PENGARUH PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Adkhiyah Adkhiyah; Yuyu Yuhana; Anwar Mutaqin (Universitas Sultan Ageng Tirtayasa, 2019)
This study aim for knowing the effect of using the learning model Student Team Achievement Division (STAD) and Learning from the problem solving skills matematica. This study is conducted at SMKN 3 Tangerang from January to May. The population in this study is the whole student of SMKN 3 Kab. Tangerang and the sample is class student eleven. The research method uses experimental design with the treatment of student group (treatments) using the learning model Student Team Achievement Division (STAD) whereas for the control class using a conventional model. As for the moderator is the motivation student are learning on mathematical subject. For data analysis using variant analysis (ANAVA) two direction at a significance level of 5%. Based on the results of the analysis came the conclusion that: (1) There is the influence of STAD's learning model of students ' mathematical problem solving skills; (2) High motivation student problem solving capability is better than students with low motivation; (3) There is no interaction between learning and motivation to the students ' mathematical problem-solving skills; (4) The influence of the learning model of STAD is better than conventional learning in high motivation students, while in low motivation does not show a significant difference.